THE IMPACT OF PARENTAL GUIDANCE DURING CLASS HOURS ON SOCIAL-EMOTIONAL DEVELOPMENT(A CASE STUDY OF 4-5 YEAR OLD CHILDREN AT RA JEMBATAN KEMBAR, LEMBAR DISTRICT) - Elda Susi Saputri (Sinar Lima, 2025)
This research was motivated by the researcher's concern regarding the impact of parental support during study hours on social-emotional development. This study employed a qualitative approach with a descriptive approach. Primary data sources included principals, teachers, parents, and children as supporting data. Secondary data sources included documentation such as observation notes and interviews, as well as photographs related to parental support during study hours on social-emotional development. Data analysis techniques used included data collection, data reduction, data presentation, and conclusion drawing and verification. Based on the research results shows that the form of parental assistance during study hours for social emotional development includes: (1) Providing learning facilities, (2) Providing motivation, (3) Monitoring the use of study time, (4) Recognizing and overcoming children's difficulties in learning. The teacher's solutions to address parents who accompany children during study hours include: First, Teachers as Informants are the first source of information at school, both academic and general information. Second, Teachers as Motivators are an important role in their interactions with students. Third, Teachers as Facilitators where teachers must provide possible facilities such as how teachers make a comfortable classroom, provide learning facilities. The indicators of social emotional development include: Self-awareness, Sense of responsibility for oneself and others, and Social behavior. The impact of parental guidance during study hours can affect the child's social and emotional development indicators.